Increasing Awareness of Saving Early Through the Use of Used Bottles as Educational Piggy Banks at SD Negeri 01 Pringrejo - Nafkha, Syahadatun; Asmahani, Inas; Cahyani, Aulia Regita; Fatkhudin, Aslam; Aisyah, Risqi Dewi (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2025)
Community service activities thru the Independent KKN (Community Service Program) 2025 in Tegalrejo Village, Pekalongan City, have successfully raised awareness among the children of Tegalrejo State Elementary School 01 about the importance of saving from an early age. Thru a creative and fun approach, children are taught to manage their finances wisely and responsibly, as well as to care for the environment by utilizing plastic bottle waste to create educational piggy banks. This activity involves regular socialization, training, and mentoring, which has proven effective in instilling saving habits and developing students' creativity. The results of the activity showed high enthusiasm from the students, with increased understanding of the concept of saving and the benefits of recycling. With good cooperation between students, the community, and village officials, this program can be completed successfully and have a positive impact on the local community.